Deficiencies in diagnosing HIV-infection during pregnancy in Brazil, 1998 - Marques, HHS (2002)
OBJECTIVE: The increasing number of women with AIDS in the state of São Paulo has lead to the implementation of a series of measures to reduce mother-to-child HIV transmission. The objective of this study was to evaluate these measures' deficiencies regarding coverage and quality of prenatal care in some HIV reference services in the state of São Paulo. METHODS: All HIV-positive women, aged 18 years or more, who gave birth in 1998 were interviewed when they came for a visit with an infectologist or a pediatrician in three cities (São Paulo, Santos and São José do Rio Preto) of the state of São Paulo. A structured questionnaire was applied. Prenatal care and time of their HIV infection diagnosis (before, during or after pregnancy) were assessed. RESULTS: Of 116 women interviewed, 109/116 (94%) had attended a prenatal care service during pregnancy, 64% had their first visit in the first trimester and 80% had 3 or more visits during pregnancy. The mean age of those who attended a prenatal service was 29.1 years, higher than those who did not attend any service (24.3 years). The HIV-positive status was known by 45%, 38% and 17% of the women before pregnancy, during pregnancy and after delivery, respectively. HIV testing was offered to 82% who did not know their serologic status, and among these, only 56% were informed about the importance of getting tested. The basic health care units (UBS) were less efficient in conveying information to the mothers about their children's infection risk (p=0.037) and their treatment needs (p=0.014). CONCLUSIONS: The main deficiencies identified were lack of HIV testing during pregnancy and inadequate information. Though basic health care units are the most important source of care for this population, its contribution to the understanding of risks and treatment needs was the most unsatisfactory.